A kinematic analysis of the Kasamatsu gastr.m.3/2 in Xing Ao-wei's Vaulting Horse - Yao, X.-W.; Li, J.; Yu, H.; Li, W. (Journal of Beijing Sport University, 2004)
This essay analyzes the internal law and technical features of Chinese excellent gymnast XING Ao-wei's movement through a kinematic research on his performance of Kasamatsu gastr.m.3/2, which will play a big role in the further development of those Kasamatsu difficult movements and the improvement of technical levels of Chinese Vaulting Horse gymnasts.